Bapel “bakso apel” the innovation of bakso that uses apple to increase the consumption of apple and bakso which can decrease the risk of cancer / Shinta Octaviana Banuarti ... [et al.] - Banuarti, Shinta Octaviana; Hindarto, Syahrul; Masruroh, Siti; Fajarista, Eka Yhunias; Auliya, Nahdliyatul; Adlom, Ahmad Faatihul Khuluqil (Universiti Teknologi MARA, Kedah, 2019)
Apple is the main fruit sector in Malang that is why Malang is usually called as the city of apple (Kota Apel). At present, abundant apple harvest are only sold in the form of fresh fruit. As a result, people especially malang people feel bored when eating apple in the same way. Meanwhile, based on research, apple can decrease the risk of colon cancer, prostate cancer and lung cancer. Apples that are rich of antioxidant compounds can take control the movement of bowel. Then, the apple fiber can be able to prevent heart disease. Based on those, apple should be eaten by people. Malang is also known as the city of bakso. In Malang, it is a normal thing that we can find traders selling bakso along the way. The high demand of bakso makes bakso business to be a lucrative business. However, the variant that is served is still similar since the first time bakso have appeared. Costumer need something new of bakso that can make bakso will be more interesting. Based on that case, writers want to make the new innovation food that is made from apple in the form of bakso. This product will be the first bakso that use apple cop as an additional dough which can increase the selling value of both apples and meatballs.